The first Bronze Age bull-headed lyre from south-east Arabia? Tantalising shell inlays from the third millennium BC (Umm an-Nar) site of al-Tikha, Sultanate of Oman - Simpson, St J. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
This paper looks at two finds from the third millennium BC site of al-Tikha. Located near the confluence of the Wadi Far and Wadi Sahtan in the southern part of the Batinah region of Oman (UTM 40Q 544200/2592100), the site was explored in detail and mapped for the first time as part of the Rustaq-Batinah Archaeological Survey directed by Dr D. Kennet (University of Durham) from 2013–2018, supported by the Anglo-Omani Society (Figure 1). It is one of only four known settlements of the Umm an-Nar period (2700–2000 BC) on the Batinah, with the most completely preserved plan of any Umm an-Nar site in south-east Arabia. This includes three monumental round towers, remains of numerous rectilinear buildings in separate clusters, a large scatter of surface pottery, a cemetery, and two further monumental structures. In total the site extends over some 50 hectares. The site is now largely covered by a modern cemetery but detailed mapping and surveys have thrown considerable light on the spatial organisation of one of the most significant third millennium BC sites in south-east Arabia, although it should be noted that there is evidence that occupation at the site continued into the first half of the second millennium (Deadman, Kennet and de Vreeze in press).